Deafness-related protein PDZD7 forms complex with the C-terminal tail of FCHSD2. Issue 12 (30th June 2022) - Wang, Huang; Zhao, Dange; Du, Haibo; Zhai, Xiaoyan; Wu, Shaoxuan; Lin, Lin; Xu, Zhigang; Lu, Qing
Abstract : In cochlea, deafness-related protein PDZD7 is an indispensable component of the ankle link complex, which is critical for the maturation of inner-ear hair cell for sound perception. Ankle links, connecting the different rows of cochlear stereocilia, are essential for the staircase-like development of stereocilia. However, the molecular mechanism of how PDZD7 governs stereociliary development remains unknown. Here, we reported a novel PDZD7-binding partner, FCHSD2, identified by yeast two-hybrid screening. FCHSD2 was reported to be expressed in hair cell, where it co-operated with CDC42 and N-WASP to regulate the formation of cell protrusion. The association between FCHSD2 and PDZD7 was further confirmed in COS-7 cells. More importantly, we solved the complex structure of FCHSD2 tail with PDZD7 PDZ3 domain at 2.0 Å resolution. The crystal structure shows that PDZD7 PDZ3 adopts a typical PDZ domain topology, comprising five β strands and two α helixes. The PDZ-binding motif of FCHSD2 tail stretches through the αB/βB groove of PDZD7 PDZ3. Our study not only uncovers the interaction between FCHSD2 tail and PDZD7 PDZ3 at the atomic level, but also provides clues of connecting the ankle link complex with cytoskeleton dynamics for exploiting the molecular mechanism of stereociliary development.